MOBILITY RELATED TO POSITIVE IMPACT OF TRANSPORT (Perner's Contacts, 2011)
The article deals with positive social impacts of transport; dividing them into external, i.e. outside a transport system, and internal – inside a transport system. Intensity of a transport system use is monitored on the background of passenger and goods mobility.
Keywords: mobility; internal benefit of transport; external benefits of transport; transport problem